Analysis of the Quality of Life of Elderly Patients With Removable Orthopedic Prostheses - Jumayev Akbar Hamidovich (American Journal of Bioscience and Clinical Integrity, 2024)
The research is devoted to the development of a methodology for orthopedic assessment of the quality of life of elderly patients in need of removable dentures belonging to various social groups of the Bukhara region. Evidence was presented that the proposed method of installing the prosthesis is more effective than the standard one and allows improving the quality of the patient’s dental life and speeding up adaptation to removable prostheses. Based on the data obtained on the analysis of the quality of life of elderly and elderly patients of different social groups before and after orthopedic dental treatment.Based on the data noted above, clinical research methods and survey results, recommendations were developed to improve the adaptation of elderly and elderly patients of different social groups to and from removable dentures.